Tepotinib Inhibits Several Drug Efflux Transporters and Biotransformation Enzymes: The Role in Drug-Drug Interactions and Targeting Cytostatic Resistance In Vitro and Ex Vivo - Vagiannis, Dimitrios; Budagaga, Youssif; Morell, Anselm; Zhang, Yu; Novotná, Eva; Skarka, Adam; Kammerer, Sarah; Küpper, Jan-Heiner; Hanke, Ivo; Rozkoš, Tomáš; Hofman, Jakub (International journal of molecular sciences, 2021)
Tepotinib is a novel tyrosine kinase inhibitor recently approved for the treatment of non-small cell lung cancer (NSCLC). In this study, we evaluated the tepotinib's potential to perpetrate pharmacokinetic drug interactions and modulate multidrug resistance (MDR). Accumulation studies showed that tepotinib potently inhibits ABCB1 and ABCG2 efflux transporters, which was confirmed by molecular docking. In addition, tepotinib inhibited several recombinant cytochrome P450 (CYP) isoforms with varying potency. In subsequent drug combination experiments, tepotinib synergistically reversed daunorubicin and mitoxantrone resistance in cells with ABCB1 and ABCG2 overexpression, respectively. Remarkably, MDR-modulatory properties were confirmed in ex vivo explants derived from NSCLC patients. Furthermore, we demonstrated that anticancer effect of tepotinib is not influenced by the presence of ABC transporters associated with MDR, although monolayer transport assays designated it as ABCB1 substrate. Finally, tested drug was observed to have negligible effect on the expression of clinically relevant drug efflux transporters and CYP enzymes. In conclusion, our findings provide complex overview on the tepotinib's drug interaction profile and suggest a promising novel therapeutic strategy for future clinical investigations.
Keywords: Drug Resistance, Multiple; nádory plic; nemalobuněčný karcinom plic; Lung Neoplasms; techniky in vitro; Humans; multidrug resistance; pyrimidiny; non-small cell lung cancer; Carcinoma, Non-Small-Cell Lung; lékové interakce; cytostatické látky; ABC transportéry; Antineoplastic Agents; Pyridazines; pyridaziny; lidé; chemorezistence; Piperidines; mnohočetná léková rezistence; cytochrome P450; Drug Interactions; drug interaction; ABC transporter; ATP-Binding Cassette Transporters; In Vitro Techniques; protinádorové látky; tepotinib; Cytostatic Agents; piperidiny; Pyrimidines; Drug Resistance, Neoplasm